Current State of Economics of Southwest Michigan Blueberries - Trattles, Sara (My University, 2019)
Highbush Blueberries are a perennial crop that typically take 4-8 years to produce fruit and 6-12 years to produce as a mature bush. Highbush blueberries account for about 98% of fresh blueberries in North America and about 46% of the processed market for US blueberry consumption. In Southwest Michigan, the blueberry industry is experiencing narrower profit margin as a result of declining product prices through oversupply from global production and increased costs of production. The economic model developed examines historical data and analyses its implications to Michigan blueberry market. Results indicate that to be able to stay in business producers need to find ways to increase per unit average production, and/or find ways to reduce costs. A sensitivity analysis is used to show the effects of changes to some of the largest expenses, labor and chemicals, and also sensitivity to income fluctuations. Income is looked at with a 10% increase or decrease to total income and pounds produced. Labor and chemical expenses were looked at with a 20% increase or decrease in costs.
Keywords: Blueberries; Economic Outlook; Michigan